Evolutionary Airfoil Shape Optimization Coupling Parameterization Methods with Lagrangian Vortex Method - Duong, Viet Dung; Duong, Viet Anh (Smart Systems and Devices, 2023)
In the present paper, the evolutionary algorithm for single-objective optimization is developed using a genetic algorithm and employing polynomial-based (PARSEC) and radial basis function (RBF) functions for NACA 2412 airfoil parameterization. The determination of the objective functions (aerodynamic coefficients) are performed using the Lagrangian vortex particle method. The results of the lift coefficient at the wide range of angle of attack using the vortex particle method shows a good agreement with experimental data listed in the literature. For the optimization results, the lift coefficient obtained from the PARSEC method is optimized to be larger for the whole range of AoAs; while it still keeps the stall region at the upper surface of the airfoil to be the same as that of the original airfoil. In addition, the RBF method illustrates the lift coefficients larger at the range of AoA from -5 to 14 but stall occurs earlier than the original airfoil.